Is a Nominee a Trustee or a Beneficiary? A Study on the Islamic Legal Maxim “In Contracts Effect is Given to Intention and Meaning and not Words and Forms” and Its Relevance to the Nomination Concept and Practice in the Administration of a Muslim’s Estate in Malaysia. - Abdullah, Mohamad Asmadi; Arifin, Mahamad; Omar, Muhammad Naim; Mohd Napiah, Mohammad Deen (INSI Publications, 2012)
In a sale transaction, parties to the contract are allowed to pronounce an offer using words which do not indicate a sale. He may use the word such as hibah in the offer as long as the nature of the contract is exchange. Nomination is a means to expedite the process of the administration of a deceased Muslim’s estate. It is commonly practiced in financial institutions such as insurance and takaful companies, Pilgrimage Fund and Employee Provident Fund. An issue arises as regard to the status of nominee, as a trustee or beneficiary. A fatwawas issued by the National Fatwa Committee in 1973 stating that a nominee acts only as a trustee. However, the decisions of the civil courts and the Shari`ah court show that a nominee could be a beneficiary. This research is undertaken to examine the Islamic legal maxim and its relevance to the principle of nomination in Malaysia. Here, even though it is a nomination form and the nominee appointed is merely a trustee according to the 1972 fatwa, the wordings of the nomination might indicate a different connotation.